The Influence of Audio Stories on Enhancing Digital Literacy In Early Childhood: A Survey Study - Bisma, Nur; Desmita, Desmita; Kharisma Diyenti, Adella; Adha Karim, Nur; Zalzabila, Zakiah; Yulia, Nova; Warmansyah, Jhoni; Sulong, Komareeyah (Indonesian Journal of Early Childhood Educational Research (IJECER), 2023)
Digital literacy in children is the ability to understand information from the various information they receive. Introducing digital literacy to children is very important, in this era children use digital technology more often. Therefore, it is important for parents to ensure that children have a good understanding of how to use technology properly and that it can be used in positive activities. The aim of this research is to find out how to use audio stories to improve digital literacy skills in children. This research can also see how parents participate in introducing digital literacy to children, this media can help children develop developmental aspects in children. This research method uses a qualitative descriptive method. The results of this research provide important knowledge about research developments related to the development of digital literacy. Children can understand listening and improving words, retelling and most importantly children can express what is on their mind and use language that is easy for children and other people to understand. Researchers can conclude that it is very important to instill digital literacy in children from a young age because this development is very important to be instilled from a young age, this development is very influential on cognitive development in early childhood.┬á┬á